The Influence of Internal Control, Green Budgeting, and Employee Participation on Environmental Accountability in Green Property Companies in Indonesia - Mahdi, Fadilla Muhammad; Hayati, Nur; Kristanto, Eri; Sudarmanto, Eko; Aulia, Triana Zuhrotun (Westscience Press, 2025)
This study investigates the influence of internal control, green budgeting, and employee participation on environmental accountability in green property companies in Indonesia. Employing a quantitative research design, data were collected from 140 respondents using a 1–5 Likert scale questionnaire. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results show that internal control has a significant positive effect on environmental accountability, demonstrating the role of strong monitoring and evaluation systems in enhancing compliance with sustainability practices. Green budgeting also exhibits a positive and significant impact, highlighting the importance of allocating financial resources toward environmentally friendly initiatives. Furthermore, employee participation significantly strengthens environmental accountability, reflecting the need for inclusive involvement in organizational decision-making related to sustainability. Overall, the findings emphasize that integrating robust governance mechanisms, environmentally oriented budgeting, and employee engagement can substantially improve environmental accountability in Indonesia’s green property sector. These results provide both theoretical contributions to sustainability research and practical recommendations for policymakers and business leaders seeking to align corporate practices with global environmental standards.